Pendampingan Sekolah dalam Pengembangan Program Sekolah Sehat dan Gerakan Kebugaran Jasmani bagi Siswa Sekolah Dasar - Rumahlewang, Emma; Matitaputty, Johanna; Latar, Idris Mohamad (Universitas Pattimura, 2024)
The increasingly sedentary lifestyle among elementary school students and low awareness of healthy behavior pose challenges in achieving a healthy school environment. This community service aims to enhance elementary schools’ capacity in developing healthy school programs and physical fitness movements through collaboration among teachers, students, parents, and health workers. The activities were conducted over a three-month period using a participatory community-based approach consisting of needs analysis, teacher training, physical activities, and collaborative evaluation. The results revealed significant improvements in healthy behavior practices, with approximately a 30% increase in students’ daily exercise habits and greater parental involvement in promoting balanced nutrition. This program produced an effective school empowerment model that integrates hygiene, nutrition, and physical activity sustainably. The implication emphasizes the importance of strengthening cross-sector collaboration between education and health institutions to foster a lasting culture of healthy schools across Indonesia’s island regions